Look back in anger - Osborne, John (Oxford university press, 1992)
Jimmy Porter is a university graduate who rejects middle class dreams and operates a candy stall in a local flea market. His wife, Alison, endures his anger and frustration because of his intense love. But when an actress friend of Alison's temporarily moves in with them, Jimmy becomes a twisted figure of bitterness and pain as disillusionment and anger overtake him